2023
DOI: 10.1021/jacs.3c00747
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Activation of C–H Bond and Inhibition of C–C Bond Cleavage by Tuning Strong Oxidative Pd Sites

Meng Guo,
Peijie Ma,
Lu Wei
et al.

Abstract: Improving the product selectivity meanwhile restraining deep oxidation still remains a great challenge over the supported Pd-based catalysts. Herein, we demonstrate a universal strategy where the surface strong oxidative Pd sites are partially covered by the transition metal (e. g., Cu, Co, Ni, and Mn) oxide through thermal treatment of alloys. It could effectively inhibit the deep oxidation of isopropanol and achieve the ultrahigh selectivity (>98%) to the target product acetone in a wide temperature range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 56 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…In order to understand the mechanism of C─Cl bond cleavage during CB oxidation, the densities of states (DOS) were examined related to CB adsorption on RuO 2 (110) (Figure 4c). [49,50] The energy levels of the Ru d orbitals near the Fermi level and the CB 𝜋* orbitals (LUMO) were compatible, resulting in the partial occupation of the newly formed d-𝜋* orbitals. According to this bonding model, the partially empty 𝜋* orbitals of the CB molecule received electrons from the metal d orbitals, thereby weakening the C─Cl bond and causing the CB molecule to have a radial nature (including an unpaired electron), which made it reactive toward dehydrogenation.…”
Section: Elimination Reaction Mechanism and Electronic Structurementioning
confidence: 99%
“…In order to understand the mechanism of C─Cl bond cleavage during CB oxidation, the densities of states (DOS) were examined related to CB adsorption on RuO 2 (110) (Figure 4c). [49,50] The energy levels of the Ru d orbitals near the Fermi level and the CB 𝜋* orbitals (LUMO) were compatible, resulting in the partial occupation of the newly formed d-𝜋* orbitals. According to this bonding model, the partially empty 𝜋* orbitals of the CB molecule received electrons from the metal d orbitals, thereby weakening the C─Cl bond and causing the CB molecule to have a radial nature (including an unpaired electron), which made it reactive toward dehydrogenation.…”
Section: Elimination Reaction Mechanism and Electronic Structurementioning
confidence: 99%
“…Such bimetallic catalysts display unique geometry coordination environments and electronic structures that are different from the parent Pt metal. In particular, Pt-based intermetallic compounds (IMCs), such as the tetragonal L10-type PtM with heterometal atoms bonded, can be varied to a limited extent while still maintaining a highly structured lattice structure with a large number of interatomic bonding bonds, accompanied by a strong d–d orbital interaction. Therefore, they have been widely used in polyol oxidation and CO 2 hydrogenation reactions. For instance, Feng et al found that the introduction of Bi to Pt can induce the formation of a Pt–Bi active structure, promoting selective oxidation of the C–H bond on glycerol. Guo et al reported that reducing the exposure of surface Pd sites by introducing Cu maintains the high C–H bond activation ability and simultaneously inhibits the C–C bond cleavage for the oxidation of isopropanol to acetone. Obviously, the Pt-based IMC shows great potential in achieving the desired activation of the C–H bond and preventing the nonselective activation of the C–O–C bond.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-solution alloy nanoparticles with atomic-scale homogeneity hold significant potential for maximizing catalytic activity and optimizing selectivity in comparison with their monometallic counterparts owing to the synergistic contributions from constituent elements. In these systems, the electronic structure can be finely regulated by successively tuning the composition of alloy nanoparticles, which results in the alteration of binding energies of reactants/intermediates onto the catalyst surfaces. Consequently, the catalytic efficiency toward a specific reaction could be promoted by accelerating the rate-determining step along the reaction pathway . Recently, the incorporation of nonprecious transition-metal elements into noble metals forming alloys with the aim to reduce cost and simultaneously enhance catalytic performance has become a cutting-edge research frontier, and the successful preparation of PtFe, RhCu, PtCo, and AuCu with superior catalytic behaviors relative to the monometallic precious metal-based catalysts have elaborated the potential of this strategy.…”
Section: Introductionmentioning
confidence: 99%